(untitled) (International Conference on Economics, Finance, Banking and Management, 2025)
Although Peter I did not directly launch invasions into Central Asia, he laid the foundation for Russia’s future colonial policy. Below is a detailed analysis of the main aspects of Russia’s attitude and activities towards the Central Asian khanates during this period.